2000
DOI: 10.1002/1521-3935(20001101)201:17<2239::aid-macp2239>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Living polymerization of phenylacetylene by rhodium-based ternary catalysts, (diene)Rh(I) complex/vinyllithium/phosphorus ligand. Effects of catalyst components

Abstract: It was proved that a Rh‐based ternary catalyst composed of [(nbd)RhCl]2 (nbd: bicyclo[2.2.1]hepta‐2,5‐diene), (triphenylvinyl)lithium, and triphenylphosphine induces living polymerization of phenylacetylene. [(nbd)RhCl]2 was effective as the main catalyst, whereas neither [(cod)RhCl]2 (cod: 1,5‐cyclooctadiene) nor [(coe)2RhCl]2 (coe: cyclooctene) induced living polymerization. The anionic ligands such as chlorine, methoxy, and acetoxy groups in the Rh complex hardly affected the living polymerization. When vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 11 publications
1
35
0
4
Order By: Relevance
“…72 %. A more detailed examination of the ligand components in this system was subsequently reported by Misumi et al [6] The first reported isolable Rh I -vinyl complexes from this family of catalysts came from Miyake, Misumi and Masuda. not requiring the use of a lithiated unsaturated species in its synthesis.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…72 %. A more detailed examination of the ligand components in this system was subsequently reported by Misumi et al [6] The first reported isolable Rh I -vinyl complexes from this family of catalysts came from Miyake, Misumi and Masuda. not requiring the use of a lithiated unsaturated species in its synthesis.…”
Section: Introductionmentioning
confidence: 66%
“…Under these conditions the resulting PPA has a theoretical M n of 25,000 at 100 % monomer conversion. The low activity is surprising; however, Misumi and co-workers [6] reported that for similar species such as (1,2-diphenyl)vinyl lithium, while still maintaining a generally low dispersity. 1 H NMR spectroscopic analysis of the obtained PPA indicated that it was highly stereoregular with a calculated [14] cis content of 96 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nach diesem ersten Bericht publizierten Misumi et al . eine detaillierte Studie zu den Auswirkungen jeder Komponente in solchen ternären katalytischen Systemen.…”
Section: Rhodium(i)‐vinyl‐komplexeunclassified
“…2-14j). Various substituted acetylenes such as phenylacetylene have also been studied [Kanki et al, 2002;Misumi et al, 2000].…”
Section: -6c Alkynesmentioning
confidence: 99%